PENGGUNAAN METODE TCSD (TASK CENTERED SYSTEM DESIGN) DALAM WEBSITE REKAM MEDIS PADA RUMAH SAKIT PELABUHAN PALEMBANG - Nyimas Sopiah; Ari Muzakir (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
Pelabuhan Hospital Palembang is one of the institutions of public health services in Palembang located at Jalan Mayor Memet Sastrawirya No.1, Palembang. The hospital had problems in the data processing that were not computerized especially on patients’ medical records unit in which the data processing were still manually and did not integrate with other data. Thus, it needed an information system of patients’ medical record that could provide convenience for employees in processing the data for patients, doctors, medicines, and so on so it could be integrated well with other data by using a local network. The writer applied the method TCSD (Task Centered System Design) in its construction which were used to identify user and task need. Based on the descriptions above, the writer raised the issue as the research for this thesis. The selected title was